Penyuluhan Pemanfaatan Sampah Organik Rumah Tangga melalui Pembuatan Pupuk Kompos dengan Metode Takakura dan Teknologi Komposter serta Ecoenzym di Desa Suci Kecamatan Panti Kabupaten Jember - Widyatami, Linda Ekadewi; Lestari, Datik; Maulana Firmansyah, Akbar; Nafisatul Mutmaina, Dini; Edwinsyah Yanuan Putra, Mohammad (J-Dinamika : Jurnal Pengabdian Masyarakat, 2026)
Suci Village, located in Panti District, Jember Regency, is one of the villages that manages a Waste Bank Unit (BSU). The village has the Larahan Makmur Waste Bank, which was established in January 2018. The establishment of BSU Larahan Makmur was partly driven by the fact that Suci Village is situated on the slopes of Mount Argopuro and is prone to natural disasters, particularly flooding. The main issue in waste management at BSU Larahan Makmur is that its activities are still focused on the management and utilization of inorganic waste, while household organic waste has not yet been utilized. Currently, a large portion of household organic waste in Suci Village is still disposed of into rivers The objectives of this community service activity are to improve the knowledge, skills, and participation of partners in utilizing household organic waste into compost. The activity was carried out through extension methods, which included: providing education on the utilization of household organic waste for compost production using the takakura method, drum composter technology, and ecoenzyme making; and practice and mentoring in compost production from household organic waste using the takakura method and drum composter technology, as well as ecoenzyme making together with the partners The results of this community service activity include: improved knowledge and skills of the partners in utilizing household organic waste for compost and ecoenzym; increased utilization of organic waste for compost production by the partners; and the handover of composter (3 units) and takakura baskets (8 baskets) to the partners.